Purification of nitrogen regulator II, the product of the glnL (ntrB) gene of Escherichia coli. - Ninfa, A J (1986)
We purified the product of glnL (ntrB), NRII, and the product of a mutant glnL allele, NRII2302. In vitro transcription of the nitrogen-regulated promoter glnAp2 by purified components of Escherichia coli required NRII or NRII2302 when the template DNA was linear.